KONTRIBUSI PEMBIAYAAN SEKTOR PERTANIAN BANK SYARIAH TERHADAP KESEJAHTERAAN PETANI DI PULAU SUMATERA PERIODE 2016-2017 - Purwanto Purwanto (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2018)
The operation of sharia banking system in Indonesia is to support the implementation of national development in order to improve justice, togetherness, and equity of welfare from people especially farmers in Sumatera. The financing of agriculture sector is conducted by sharia banking in Sumatera in the last two years (2016-2017) has always increased. The existence of financing disbursed in the agricultural sector can improve the welfare of farmers. Farmers' welfare in this study is projected by Farmer's Exchange Value or FEV which is the ratio between the price index that is received by farmers and the price index that is paid by farmers. Therefore the purpose of this study is to test whether there is a significant and positive influence between agricultural sector financing that is conducted by BUS and UUS on the island of Sumatera 2016-2017. Second, to test whether there is a significant and positive influence between agricultural sector financing that is conducted by BPRS on the island of Sumatera 2016-2017. The type of this study is explanatory that is conducted to prove the causal relationship and to test how the influence between one variable with others. The type of data that is used is secondary data in a monthly form. This paper use panel data regression analysis to answer the research questions. The result finds that financing of the agricultural sector that is conducted by BUS and UUS on the island of Sumatera in 2016-2017 has no significant effect on the welfare (value Prob 0,6563> 0.05). This paper also finds that the agricultural financing that is conducted by BPRS in Sumatera island 2016-2017 has a negative effect on the welfare of farmers in Sumatera (value Prob 0.0004 <0.05).===============================================Beroperasinya sistem perbankan syariah di Indonesia adalah untuk menunjang pelaksanaan pembangunan nasional dalam rangka meningkatkan keadilan, kebersamaan, dan pemerataan kesejahteraan rakyat tidak terkecuali para petani di Sumatera. Pembiayaan sektor pertanian yang dilakukan perbankan syariah di Sumatera dua tahun terakhir (2016-2017) selalu mengalami peningkatan. Adanya pembiayaan yang disalurkan pada sektor pertanian maka dapat meningkatkan kesejahteraan petani. Kesejahteran petani dalam studi ini diproxykan dengan Nilai Tukar Petani atau NTP yang merupakan rasio antara indeks hargayang diterima petani dengan indeks harga yang dibayar petani. Maka dari itu tujuan dari studi ini adalah pertama menguji apakah ada pengaruh signifikan dan positif antara pembiayaan sektor pertanian yang dilakukan oleh BUS dan UUS di pulau Sumatera tahun 2016-2017. Kedua untuk menguji apakah ada pengaruh signifikan dan positif antara pembiayaan sektor pertanian yang dilakukan oleh BPRS di pulau Sumatera tahun 2016-2017.Jenis studi ini adalah eksplanatori yaitu studi yang dilakukan untuk membuktikan hubungan sebab akibat dan untuk menguji bagaimana pengaruh antara variabel satu dengan variabel. Jenis data yang digunakan adalah data skunder dalam bentuk bulanan. Adapun analisis data menggunakan analisis regresi data panel. Hasil dari studi ini adalah pertama pembiayaan sektor pertanian yang dilakukan oleh BUS dan UUS di pulau Sumatera tahun 2016-2017 tidak berpengaruh signifikan terhadap kesejahteraan petani (nilai Prob 0, 6563 > 0,05). Kedua hasil analisis membuktikan jika pembiayaan sektor pertanian oleh BPRS di pulau Sumatera tahun 2016-2017 berpengaruh negatif terhadap kesejahteraan petani di Sumatera (nilai Prob 0.0004 <0,05).